The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s19194065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Soybean Varieties Using Hyperspectral Imaging Coupled with Convolutional Neural Network

Abstract: Soybean variety is connected to stress resistance ability, as well as nutritional and commercial value. Near-infrared hyperspectral imaging was applied to classify three varieties of soybeans (Zhonghuang37, Zhonghuang41, and Zhonghuang55). Pixel-wise spectra were extracted and preprocessed, and average spectra were also obtained. Convolutional neural networks (CNN) using the average spectra and pixel-wise spectra of different numbers of soybeans were built. Pixel-wise CNN models obtained good performance predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Seed identification technology based on spectral reflectance has gradually developed, but image-based seed identification technology has not achieved satisfactory results. With the development of computer technology and information technology, the automatic identification of seed varieties and quality by machine vision combined with deep learning is an inevitable trend [20,63,64]. Moreover, hyperspectral technology is not limited to seed identification.…”
Section: Resultsmentioning
confidence: 99%
“…Seed identification technology based on spectral reflectance has gradually developed, but image-based seed identification technology has not achieved satisfactory results. With the development of computer technology and information technology, the automatic identification of seed varieties and quality by machine vision combined with deep learning is an inevitable trend [20,63,64]. Moreover, hyperspectral technology is not limited to seed identification.…”
Section: Resultsmentioning
confidence: 99%
“…The source dataset in this study was much larger than all the datasets in their study and was enough for VGG-MODEL training. For structures like ResNet, Zhu et al (2019) compared the performance of a developed ResNet with a general deep convolutional neural network on a cotton dataset. Also, they found that ResNet was not as effective as the latter one.…”
Section: Classification Results On Source Datasetmentioning
confidence: 99%
“…The source dataset in this study was much larger than all the datasets in [43] and was enough for VGG-MODEL training. For structure like ResNet, [44] compared the classification accuracy of a developed ResNet with a general deep convolutional neural network on cotton datasets, and also found that…”
Section: Identification Results Analysis On Source Datasetmentioning
confidence: 99%